2019
DOI: 10.1038/s41598-019-44335-8
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic two-step photoexcitation effects in intermediate-band solar cells with quantum dot-in-well structure

Abstract: We studied the dynamics of electrons generated by two-step photoexcitation in an intermediate-band solar cell (IBSC) comprising InAs/GaAs/Al 0.3 Ga 0.7 As dot-in-well (DWELL) structure using time-resolved photocurrent (TRPC) measurement. The examined IBSC exhibited considerably slower photocurrent decay than a conventional InAs/GaAs quantum dot IBSC, which is due to the extraordinarily long-lived electrons in the DWELL. In order to retrieve the electron lifetime fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…It is noted that the nonradiative component is overestimated because we do not take into account the weak PL from the InAs wetting layer and the GaAs in our analysis. Within the accuracy of our assumptions, we find that 7% of the photogenerated carriers in the GaAs are collected via TPU in our device at −0.6 V. As J p is generated by adiabatic excitation in the TPU process, it is expected that the output voltage will be boosted [36]. Figure 5(c) compares the voltage increase V that is induced by the TPU process and the IR-induced J p as a function of the bias voltage.…”
Section: Evaluation Of Absolute Carrier Collection Efficiencymentioning
confidence: 53%
“…It is noted that the nonradiative component is overestimated because we do not take into account the weak PL from the InAs wetting layer and the GaAs in our analysis. Within the accuracy of our assumptions, we find that 7% of the photogenerated carriers in the GaAs are collected via TPU in our device at −0.6 V. As J p is generated by adiabatic excitation in the TPU process, it is expected that the output voltage will be boosted [36]. Figure 5(c) compares the voltage increase V that is induced by the TPU process and the IR-induced J p as a function of the bias voltage.…”
Section: Evaluation Of Absolute Carrier Collection Efficiencymentioning
confidence: 53%
“…While room temperature two-photon photocurrent (TPP) results have been reported previously, [4][5][6][7][18][19][20][21] they were measured with steady state illumination schemes whose validity has come into question due to the likelihood of thermal artefacts. [22] Here we developed a high-speed double-demodulation two-photon spectroscopy setup (see Experimental Section) to measure the TPP, and to verify that its dynamical characteristics evidenced an electronic and not a thermal origin.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] A third set of energy states is introduced between the valence band (VB) and conduction band (CB) often termed "Intermediate Band" (IB), so that electrons can be promoted from the VB to CB by the sequential two-photon absorption (STPA) of photons with energies below the bulk bandgap, in a way that generates additional photocurrent and increases the theoretical efficiency limit to 46.7% under one sun. [2] A number of physical implementations have been trialed, [3][4][5][6][7] however, the presence of the IB often leads to additional non-radiative recombination channels. [8][9][10][11][12] Vaquero-Stainer et al demonstrated the successful operation, albeit at low temperature, of a quantum ratchet IBSC (QR-IBSC) using a quantum well superlattice (QWSL).…”
Section: Introductionmentioning
confidence: 99%
“…13,14) By employing a more casual device design, we reported that IBSCs based on quantum dots-in-a-well (DWELL) structures can be also promising. [17][18][19][20][21] In our Al 0.3 Ga 0.7 As p-i-n single-junction SC containing GaAs/ InAs/GaAs DWELL layers, the two-step excitation process occurs via a quantum well (QW) interband transition and a following QD intraband transition. There is a ratchet-like band alignment that deeply confines the photoexcited electrons after the QW interband excitation because these electrons are expected to undergo a quick relaxation from the QW to the QD before a second photon is absorbed.…”
Section: Introductionmentioning
confidence: 99%